2015
DOI: 10.1007/s00134-015-3897-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrical pharyngeal stimulation for dysphagia treatment in tracheotomized stroke patients: a randomized controlled trial

Abstract: In this pilot study, EPS enhanced remission of dysphagia as assessed with fiberoptic endoscopic evaluation of swallowing (FEES), thereby enabling decannulation in 75% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 35 publications
6
81
0
5
Order By: Relevance
“…The results of this and of a preceding study by our group suggest that in addition to stimulation driven motor-cortical reorganization, restoration of peripheral sensory feedback may play a role here. Thus, in line with our previous study [27], we observed a slight decline of stimulation intensities in patients showing clinically relevant treatment response, which might be interpreted as partial recuperation of the afferent sensory system induced by PES. More importantly, however, the close relation of SP increase and successful PES treatment alludes to a causal role of SP in the underlying physiological mechanism.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The results of this and of a preceding study by our group suggest that in addition to stimulation driven motor-cortical reorganization, restoration of peripheral sensory feedback may play a role here. Thus, in line with our previous study [27], we observed a slight decline of stimulation intensities in patients showing clinically relevant treatment response, which might be interpreted as partial recuperation of the afferent sensory system induced by PES. More importantly, however, the close relation of SP increase and successful PES treatment alludes to a causal role of SP in the underlying physiological mechanism.…”
Section: Discussionsupporting
confidence: 79%
“…Based on the proof-of-principle study in 2010 [37], PES is usually applied as single treatment cycle comprising 3 stimulations on 3 consecutive days [27, 30, 38]. The present study provides the first data to re-evaluate this standard procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurostimulation strategies for the treatment of post-stroke dysphagia have been employed with variable degrees of success. A recent RCT in severely dysphagic tracheotomized patients found that electrical pharyngeal stimulation was significantly associated with improved airway protection and resolution of the dysphagia; it also facilitated decannulation in the majority of patients [19].…”
Section: Strokementioning
confidence: 99%